Additives and methods for the mitigation of methane emission from stored liquid manure. (May 2023) - Ambrose, Herald Wilson; Dalby, Frederik R.; Feilberg, Anders; Kofoed, Michael V.W.
Abstract : The storage of liquid manure (slurry) is a major source of methane (CH4 ) and thus contributes significantly to the climate impact of agriculture. The necessity to store slurry in barns and storage tanks at different seasons has led to increasing research in the mitigation of CH4 emissions from the manure management chain. In this review, a holistic view of CH4 mitigation strategies targeting slurry pits and storage tanks classified based on the mechanism of interaction (physical, chemical, and biological) with slurry and their CH4 mitigation efficiency is presented. Also, the combination of chemical additives with other methods is discussed. The key methods include slurry cover, solid–liquid separation, acidification, antimicrobial agents, and aeration. Among various methods, acidification to pH 5.5 acts as a benchmark since it achieves a reduction in CH4 emission in the range of 95–99% and 65–99% from stored pig slurry and cattle slurry, respectively. Other chemical treatments such as antimicrobial agents and oxidants also reduce CH4 in a wide range depending on efficiency and dosage. Further, the combination of acidification with physical and chemical treatments yields a cumulative or synergistic effect in reducing the CH4 emission. This review identifies significant factors that influence the efficiency of the additives, which helps to mitigate CH4 emissions from slurry storage. Based on mitigation efficiency, acidification is a good choice of technology to reduce CH4 emissions from slurry storages. This technology would fit well with frequent removal of slurry from the barn to the outside storage in cold regions. Highlights: Acidification acts as a benchmark in mitigating methane emissions in stored slurry. Efficacy of chemical additives to mitigate methane emissions varied with dosage. Physical methods show reduced mitigation efficiency compared to acidification. Biological methods result in other gaseous emissions affecting implementation. Combination of chemical additives increased mitigation efficiency.